Therapeutic Effect of Combining Anisodamine With Neostigmine on Local Scar Formation Following Roux-en-Y Choledochojejunostomy in a Novel Rat Model - Lyu, Shao-cheng; Wang, Jing; Xu, Wen-li; Wang, Han-xuan; Pan, Fei; Jiang, Tao; He, Qiang; Lang, Ren (Frontiers in Pharmacology, 2021)
Backgroud: The present study aimed to explore the potential effect of combining anisodamine with neotigmine on local scar formation following Roux-en-Y choledochojejunostomy (RCJS) in a novel rat model. Methods: The biliary obstruction model of Sprague-Dawley (SD) rats was established in advance, and 54 rats were divided into 9 groups randomly (sham operation group, anisodamine groups, neostigmine groups, combination groups and control groups). Anisodamine (25mg/kg) and neostigmine (50μg/kg) were injected to abdominal cavity separately or simultaneously for 1 week since the first day after surgery according to their allocated intervention while the same amount of saline (0.5ml) were injected intraperitoneally in control group. Indexes including body weight, diameter of common bile duct, liver function, inflammatory indexes and the condition of scar formation in different groups at certain time were evaluated in our study. Results: Recovery of liver function (ALT, AST, TB, DB, GGT) and systematic inflammation indexes (CRP, TNF-α, IL-1β) in combination groups were prior to the control group (P<0.05) while no statistical difference in serum level of IL-10 was observed among groups. Rats in combination group represented a wider anastomotic diameter and lower expression of α-SMA and TGF-β1 at anastomotic stoma compared to the control group as well (P<0.05). Histopathological staining showed slighter proliferation of collagen and smooth muscle fibers in rats’ bile duct wall and less local scar formation at anastomotic stoma compared to the control group. Conclusion: The combination of anisodamine and neostigmine can alleviate local and systemic inflammatory response, promote the recovery of liver function and reduce scar formation in rats after RCJS procedure.